Produção e qualidade de milho-silagem na safra e safrinha, num sistema de integração lavoura-pecuária, em plantio direto - Bitencourt Junior, Darcy (2010)
The first experiment was carried out from May 29, 2006 to June 4, 2008. The objective was to evaluate the yield and agronomic characteristics of corn AS32 for ensiling as affected by early and late planting and the effect of grazing with dairy cows (starting when forage availability was at least 1,500 kg/ha of DM and finishing when residual plant height ranged from 7-10 cm) or mechanical harvesting (no grazing) on winter pasture, grown before corn, in straw in direct planting in an integrated crop-animal system. Experimental design consisted of split-split randomized complete blocks, with three replications. Data were submitted to analysis of variance (factorial 2x2x2 Years x Season x Cutting regimes). Harvesting criterium for corn plants evaluation and ensiling was made at the stage farinaceous hard grain. The second experiment was carried out from May 29, 2006 to June 4, 2008. The objective was to evaluate: (a) silage quality and (b) fermentative parameters, of corn AS32 for ensiling as affected by early and late planting on winter pasture desiccated straw, in direct planting in an integrated crop-animal system. Corn crops were sown in Oct 30, 2006; Nov 16, 2007 and Jan 16, 2007; Feb 06, 2008. Mechanical harvest was made at 15cm residual heights of plants, at the stage of farinaceous hard grain, and finely chopped to 1.5 cm particles size, and ensiled in experimental silos (3.5 kg). The experimental design consisted of completely randomized blocks, with three replications and subplots consisting of planting times (early and late). Data were submitted to analysis of variance, in factorial 2x2 scheme (years x times of plantings) and means compared by Tukey Test (P<0.05). Dry matter yield of normal planting date of corn was higher than for the alternative planting date; grazing, had no effect on dry matter yield . Corn cultivar AS32 recommended haversting stadium (farinaceous hard grain) presented variations in dry matter content of silage according to the year of cropping. Plant components proportions of green matter are different from the standard recommended for high quality corn silage. Fermentative and nutritional parameters showed adequate and acceptable values within the recommended patterns, either for early planting time as for late planting for AS32 hybrid grain corn-silage purpose. Cell wall components (NDF and ADF) showed acceptable values, although ADF remained slightly above of the ideal limit desired for both early and late ensiling of AS32 corn hybrid.